Development of a Clinical Framework for the Assessment of Dyskinesia and Function in the Upper Limb in Children with Cerebral Palsy. (2nd January 2023) - Ralph, Edward; Carroll, Kate; Danks, Marcella; Harvey, Adrienne
Abstract: Objective: Dyskinesia in cerebral palsy (CP) is a complex movement disorder that can significantly impact upper limb function. Despite a range of available tools, there is no consensus on best practice assessment of upper limb function in children with CP and dyskinesia. This study aimed to develop a clinical framework for the assessment of the impact of dyskinesia on upper limb function in children with CP. Design: Modified Delphi study using expert consensus. Methods: An expert panel of six highly experienced Australian therapists ranked assessment tools sourced from existing evidence-based literature using a five-point Likert scale. Tools rated as important for use "most" or "all" of the time, by 80% of respondents were accepted into the framework following two survey rounds and a third stage discussion. Results: Of 21 tools, 12 were included in the framework under five categories: (i) screening for dyskinesia; (ii) measuring the severity of dyskinesia; (iii) Classifying upper limb functional ability; (iv) measuring upper limb functional ability; and (v) measuring upper limb movement. Conclusions: The framework for assessing the impact of dyskinesia on upper limb function in CP aims to guide clinicians to improve assessment consistency and facilitate individualized goal-directed management. Further studies with a larger number of expert clinicians and researchers will further strengthen the utility of the framework.